Les « méchantes » de la fiction criminelle édouardienne de L.T. Meade et Robert Eustace : Sympathy for the (she)devil ? - Charlotte Arnautou (Contextes)
This article focuses on novels by children’s author L.T. Meade serialized in the English press at the end of the 19th century: the “villainesses” they portray constitute a feminized version of the archetypal villain of criminal fiction. Drawing on cultural studies and the theory of fictional immersion, this article highlights the way in which readers’ emotional involvement with these female characters at odds with the Patmorian ideal of the “angel in the house”, undermines the traditionally conservative values of detective fiction.